An introduction to surfactants - Tadros, Tharwat F., 1937- (De Gruyter, 2014)
Surfactants are surface active agents, molecules that have a significant role in emulsions, suspensions, and foams. They find widespread application in personal care, cosmetics, pharmaceuticals, agrochemicals and the food industry. Their classification, physical properties, phase behavior, their effects and applications are covered in this book.
Keywords: Surface active agents -- Analysis.; Surface active agents.; elektronické knihy; electronic books